Theoretical and Experimental Studies of Electrical Parameters : Irradiance G and Temperature T Effects - SORY, Mamadou Osias; SAM, Raguilignaba; DIASSO, Alain (European Journal of Applied Sciences, 2021)
The present work explores the effects of temperature T and irradiance G on electrical parameters as serie resisrance, fill factor and conversion efficiency within the base region of p-n junction of a polycristaline solar cell. This work is conducted in two forms as a theoretical study and an experimental study. Indeed, the solar cell is submitted firstly to various temperature and secondly to various irradiance values. From a theoretical approach based on the single exponential model theory, the I − V equation expression is estabilished. This expression taking account implicitely G and T . This equation I − V permits to developp Matlab script to calculate I − V and P − V values versus T and G. The serie resisrance, fill factor and conversion efficiency values versus T and G are then deducted and analyzed. From a simple experimental setup permitting I − V values measurements , the experimental values of serie resistance, fill factor and conversion efficiency are calculated and also analyzed. First, these theoretical and experimental results are in good agreement and secondo are in good agreement with those of the literature.